1988
DOI: 10.1111/j.1365-246x.1988.tb03429.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of some synthetic sub-micron magnetites

Abstract: The grain size dependence of various mineral (rock) magnetic parameters has been determined, using a series of essentially pure, fine-grained (single-domain, SD) and ultrafine-grained (superparamagnetic, SP) magnetites. The parameters measured include low-field susceptibility (x), frequency-dependent x(xFD), saturation remanence (SIRM), anhysteretic susceptibility (xARM), and coercivity of remanenceThe magnetites were produced in experiments designed to simulate possible pedogenic and biogenic pathways of magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
543
1
12

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 726 publications
(593 citation statements)
references
References 27 publications
37
543
1
12
Order By: Relevance
“…SP particles do not carry a stable remanence; therefore the P 1 component with a peak at 25 mT only reflects the concentration of magnetite/maghemite with SD size. Eyre (1996) and Spassov et al (2003a, b) reported higher coercivities of 30-35 mT for the low coercivity component in Chinese paleosols, but our value is consistent with the 21-29 mT range reported for synthetic SD magnetite (Maher, 1988). The high surface area to volume ratio of pedogenic particles makes them easy to oxidize into maghemite (van Velzen and Dekkers, 1999;Liu et al, 2003), which might explain the slightly higher coercivities documented by Eyre (1996) and Spassov et al (2003a, b).…”
Section: Analysis Of Coercivity Componentssupporting
confidence: 82%
“…SP particles do not carry a stable remanence; therefore the P 1 component with a peak at 25 mT only reflects the concentration of magnetite/maghemite with SD size. Eyre (1996) and Spassov et al (2003a, b) reported higher coercivities of 30-35 mT for the low coercivity component in Chinese paleosols, but our value is consistent with the 21-29 mT range reported for synthetic SD magnetite (Maher, 1988). The high surface area to volume ratio of pedogenic particles makes them easy to oxidize into maghemite (van Velzen and Dekkers, 1999;Liu et al, 2003), which might explain the slightly higher coercivities documented by Eyre (1996) and Spassov et al (2003a, b).…”
Section: Analysis Of Coercivity Componentssupporting
confidence: 82%
“…High percentages ( s 6%) of frequency-dependent susceptibility (measured at 0.47 and 4.7 kHz) re£ect the presence of signi¢cant numbers of superparamagnetic (SP) ferrimagnetic grains, with grain diameters 6 V20 nm (e.g. Bean and Livingston, 1959;Dunlop, 1981;Maher, 1988;Dearing et al, 1996). Fig.…”
Section: Magnetic Measurementsmentioning
confidence: 99%
“…Magnetic susceptibility is often used as an indicator for ferrimagnetic mineral concentration due to the particle size independence of this parameter [Heider et al, 1996] and because para-and antiferromagnetic minerals generally make a minor magnetic contribution to susceptibility [Thompson and Oldfield, 1986]. Magnetite percentage was calculated considering a value of 660 Â 10 À6 m 3 kg À1 for pure multidomain magnetite [Maher, 1988]. The ARM/ IRM ratio is a common magnetic grain size proxy, which is proportional to the relative content of single domain (SD) particles e.g., for equidimensional magnetite, the (30-100 nm grain size range) and pseudo-single domain (PSD) magnetite (i.e., the 100 nm-1 mm size range) [Muxworthy and Williams, 2006].…”
Section: Environmental Magnetic Analysesmentioning
confidence: 99%